Indigenous Toddlers Stunting: Ethnographic Study in Tehit and Yaben Tribes, West Papua - Isti Kumalasari; Septa Agung; Gurendro Putro (Universitas Pendidikan Indonesia, 2020)
Stunting shows nutritional problems that are chronic and last long time, such as poverty, unhealthy behavior, poor parenting/ feeding patterns since the child was born. This study aims to analyze the cultural aspects that influence the incidence of stunting under five in Tehit and Yaben Tribes, South Sorong, West Papua. This research uses ethnographic method during 45 days. Data were collected through participatory observation, in-depth interviews, direct observation supported by visual data (photos, videos), secondary data and literature study. Thematic analysis by comparing secondary data and literature study used in this study. Family parenting, consumption of toddlers, unhealthy behaviour and environment, and infection are themes that considered related to stunting. It is important for the government to provide education related to parenting and fulfilling family nutrition through sustainable development.